Impact of students assistance policies on quality of life and mental health - dos Santos de Brito, Lara; Pereira, Tiago Novaes; dos Santos, Emerson Roberto; de Barros, Thales Guardia; Martinez, William Donegá; dos Santos, Loiane Letícia; Brienze, Vânia Maria Sabadoto; de Abreu Lima, Alba Regina; Bizotto, Thaís Santana Gastardelo; André, Júlio César (Frontiers in Psychology, 2023)
Introduction: Student assistance policies in higher education, in their various modalities, seek to reduce the dropout of a new profile of students, non-traditional, with socioeconomic weaknesses, promoting quality of life and mental health during the university journey. In this context, the Student Social Support Center (C.A.S.A.) promotes assistance to students who need personal and/or economic support. Objectives: To evaluate the Quality of Life (QoL) and the presence of Minor Mental Disorders (MMD) in students from the 1st to the 4th year of medicine at a public college in Brazil, comparing C.A.S.A beneficiaries and non-beneficiaries. Materials and Methods: Cross-sectional study with 283 students. SRQ-20 and WHOQOL-Bref questionnaires were used, in addition to a questionnaire addressing sociodemographic data. Results: The general average of QoL was regular in the four evaluated domains (physical, psychological, social relationships, environment) and 55.5% of the students have evidence of MMD, in which the QoL scores are lower in all domains. The environment domain, which discusses socioeconomic conditions, has the worst score among C.A.S.A. beneficiaries and the best among C.A.S.A. non-beneficiaries. Discussion: The data corroborate the fragile situation of mental health and QoL of medical students. The student assistance modality of the analyzed program possibly presents vulnerabilities in its performance since the environment domain, the one with the lowest score among the program beneficiaries, precisely encompasses financial resources, access to goods and leisure and the individual's physical environment.